UNA PROPUESTA DE DIETA DIGITAL: REPENSANDO EL CONSUMO MEDIÁTICO EN LA ERA DE LA HIPERCONECTIVIDAD - Javier SERRANO-PUCHE (Fonseca, Journal of Communication, 2023)
The current communicational scenario is characterised by the information overload. This is definitely a distinctive feature of our age, together with the culture of speed. The increasing implementation of digital technology and the widespread of mobile devices with internet access (smartphones, tablets, etc.) have brought about the idea of `total conectivity’ not only as a technically feasible state but also as a desirable one.